THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT ON THE EFFECT OF SERVANT LEADERSHIP ON PERFORMANCE - Muji Rahayu; Saptono Kusdanu Waskito (Jurnal Ekonomi, 2022)
This study aims to determine the mediating effect of organizational commitment that bridges the positive effect of servant leadership on performance. The method used uses a quantitative, descriptive and verification approach. Data collection using a questionnaire with random sampling technique. Respondents were lecturers at 30 private universities in West Java. Mediation analysis using SPSS plug-in Process Macro A. F. Hayes. The results of the analysis show that servant leadership has a positive effect on performance, organizational commitment has a positive effect on performance and organizational commitment has a positive mediating effect on the effect of servant leadership on performance. This means that when the organizational commitment of lecturers is high, the performance achieved will be higher. This result can be interpreted that the higher the level of organizational commitment owned by lecturers, the higher the positive effect of servant leadership on the level of lecturer performance.